That's got 'em! : the life and music of Wilbur C. Sweatman - Berresford, Mark. (Jackson : University Press of Mississippi, 2010)
Wilbur C. Sweatman (1882-1961) is one of the most important, yet unheralded, African. American musicians involved in the transition of ragtime into jazz in the early twentieth. century. In That's Got 'Em!, Mark Berresford tracks this energetic pioneer over a. seven-decade career. His talent transformed every genre of black music before the. advent of rock and roll?"pickaninny" bands, minstrelsy, circus sideshows, vaudeville. (both black and white), night clubs, and cabarets. Sweatman was the first African. American musician to be offered a long-term recording contract, and he dazzle
In defense of Wilbur Sweatman : a response to his critics -- Missouri childhood -- "Pickaninnies," Ernest Hogan, and a world tour -- Circus and minstrelsy : touring life with Cornet Kings P.G. Lowery and W.C. Handy -- The anchorage for the world's marvels : the Minneapolis years -- Chicago and an entertainment revolution -- The original and much-imitated ragtime clarinetist -- Ev'rybody's crazy 'bout the doggone blues -- Rainy day blues -- The ragtime dinosaur -- The daddy of the clarinet -- The silent years.
Includes list of known compositions by Sweatman.
Includes discography (p. 188-208), bibliographical references (p. 222-225), and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
This edition in English.
WorldCat record variable field(s) change: 050, 082
Keywords: Sweatman, Wilbur C. S; Sweatman, Wilbur C. S; Clarinetists -- United States -- Biography; African American jazz musicians -- Biography; Jazz -- History and criticism; Vaudeville -- United States -- History -- 20th century; BIOGRAPHY & AUTOBIOGRAPHY -- Composers & Musicians; MUSIC -- Genres & Styles -- Jazz; African American jazz musicians; Clarinetists; Jazz; Vaudeville; United States; 1900-1999; Electronic books; Biographies; Criticism, interpretation, etc; History